Albendazole versus praziquantel in the treatment of neurocysticercosis: a meta-analysis of comparative trials. - Dimitrios K Matthaiou; Georgios Panos; Eleni S Adamidi; Matthew E Falagas (Public Library of Science (PLoS), 2008)
Background Neurocysticercosis, infection of the brain with larvae of Taenia solium (pork tapeworm), is one of several forms of human cysticercosis caused by this organism. We investigated the role of albendazole and praziquantel in the treatment of patients with parenchymal neurocysticercosis by performing a meta-analysis of comparative trials of their effectiveness and safety. Methods and principal findings We performed a search in the PubMed database, Cochrane Database of Controlled Trials, and in references of relevant articles. Six studies were included in the meta-analysis. Albendazole was associated with better control of seizures than praziquantel in the pooled data analysis, when the generic inverse variance method was used to combine the incidence of seizure control in the included trials (patients without seizures/[patients x years at risk]) (156 patients in 4 studies, point effect estimate [incidence rate ratio] = 4.94, 95% confidence interval 2.45-9.98). In addition, albendazole was associated with better effectiveness than praziquantel in the total disappearance of cysts (335 patients in 6 studies, random effects model, OR = 2.30, 95% CI 1.06-5.00). There was no difference between albendazole and praziquantel in reduction of cysts, proportion of patients with adverse events, and development of intracranial hypertension due to the administered therapy. Conclusions A critical review of the available data from comparative trials suggests that albendazole is more effective than praziquantel regarding clinically important outcomes in patients with neurocysticercosis. Nevertheless, given the relative scarcity of trials, more comparative interventional studies--especially randomized controlled trials--are required to draw a safe conclusion about the best regimen for the treatment of patients with parenchymal neurocysticercosis.